An Appraisal of the Chronology Problem in the “Rise of the West” Question - Gürsu Galip Gürsakal; Sezgin Kaya (Gazi Akademik Bakış)
“Rise of the West”, “Grand Question”, “The Great Divergence” are all different nomenclature for a pristine problematic in social sciences: The supposed discrepancy between the “East” and the “West” in a variety of domains whereby the “West” is assumed to acquire supremacy over the “East”. In the former part of our essay we try to acquaint the reader with the aforementioned literature. We do not intend to present a detailed account but just the important milestones delineating only the broadest contours of the discussion. After providing a general overview of the “Rise of the West” literature we dwell upon the “Problem of Chronology” haunting it. We call it the “Problem of Chronology” since it is essentially providing an adequate answer to the following question “When had the West Risen?” We think the researchers have too much engaged in providing an answer to the “Why” question, which is both harder to address and prone to much prejudice. According to us, a better approach is to put “Problem of Chronology” as the central piece of the argument. It is a clear cut and more tangible question to tackle. However, we pinpoint that, providing a solution to the problem requires answering a preliminary question: “In which domains should we seek a chronology?” We argue that a three pronged approach derived from Mann’s theory of social power and realist International Relations theory may be useful in achieving a methodologically satisfactory solution to the problem.